2022
DOI: 10.3390/ijms23137193
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of Surface Trans-Sialidases in Extracellular Vesicles of the Parasite Trypanosoma cruzi Using Atomic Force Microscopy (AFM)

Abstract: Trans-sialidases (TS) are important constitutive macromolecules of the secretome present on the surface of Trypanosoma cruzi (T. cruzi) that play a central role as a virulence factor in Chagas disease. These enzymes have been related to infectivity, escape from immune surveillance and pathogenesis exhibited by this protozoan parasite. In this work, atomic force microscopy (AFM)-based single molecule-force spectroscopy is implemented as a suitable technique for the detection and location of functional TS on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…We hypothesized that the theront releases these enzymes to induce necrosis of fish epithelial cells. Similar mechanisms have been reported in other parasites, including Taxoplasma [ 35 ], Plasmodium [ 36 ], and Trypanosoma [ 37 ]. In addition, we found 14 proteins in the leishmanolysin family specifically expressed in the theront and trophont stages (Table S1).…”
Section: Discussionsupporting
confidence: 79%
“…We hypothesized that the theront releases these enzymes to induce necrosis of fish epithelial cells. Similar mechanisms have been reported in other parasites, including Taxoplasma [ 35 ], Plasmodium [ 36 ], and Trypanosoma [ 37 ]. In addition, we found 14 proteins in the leishmanolysin family specifically expressed in the theront and trophont stages (Table S1).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, the characterization and functional assays (Cronemberger‐Andrade et al., 2020 ; Gutierrez et al., 2022 ; Nogueira et al., 2015 ) and the detection of biomarkers (Madeira et al., 2021 , 2022 ) can be performed. Osuna group (Prescilla‐Ledezma et al., 2022 ) suggested that EVs isolated from tissue‐culture derived trypomastigotes can be characterized using AFM‐based single molecule‐force spectroscopy as a suitable technique for the detection and location of functional components on the surface of EVs. To detect trans‐sialidase (TS) and other specific genes in EVs, it is possible to use specific monoclonal antibodies.…”
Section: Methodologies To Isolate and Characterize Evs Purification F...mentioning
confidence: 99%
“…To detect trans‐sialidase (TS) and other specific genes in EVs, it is possible to use specific monoclonal antibodies. For example, it has been shown the presence of TS using coupled antibodies to sensors (Prescilla‐Ledezma et al., 2022 ). The components present in T. cruzi EVs obtained with different methodologies, their characterization, and the biological function are summarized in Table 1 .…”
Section: Methodologies To Isolate and Characterize Evs Purification F...mentioning
confidence: 99%
“…Extracellular vesicles are lipid bilayer nanoparticles that mainly comprise exosomes and microvesicles. EVs released by T. cruzi contain several virulence factors, such as trans-sialidases, peptidyl-prolyl cis-trans isomerase, oligopeptidases and proteases [130,[132][133][134]. In addition to EVs secreted by the parasite, EVs coming from infected host cells or cells in contact with the parasite also participate in communication (Figure 4).…”
Section: Preference or Restriction To A Certain Host Tissue? Factors ...mentioning
confidence: 99%